Hubungan Tingkat Kecemasan Dengan Tingkat Kemandirian Adl (Activity Of Daily Living) Pada Lansia Di Panti Sosial Tresna Werdha Pagar Dewa Kota Bengkulu - Ice Febriantami; Des Metasari; Emi Pebriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The elderly are an age group whose numbers continue to increase. Based on data from the Central Statistics Agency, the percentage of the elderly population in Indonesia increases every year, causing various physical and psychological health problems, one of which is anxiety. Anxiety can affect the elderly's ability to perform Activities of Daily Living (ADL) thus impacting the level of independence and quality of life, especially for the elderly living in social institutions. The purpose of this study was to determine the relationship between anxiety levels and the level of independence in Activities of Daily Living in the elderly at the Tresna Werdha Pagar Dewa Social Institution in Bengkulu City. This study used a quantitative descriptive design with a cross-sectional approach. The population was 62 and the sample was 58 elderly with a total sampling technique. The instruments used were the Hamilton Anxiety Rating Scale (HARS) and the Barthel Index. Data analysis used the Chi-Square test. The results showed that the majority of elderly experienced mild anxiety (77.6%) and the majority were in the independent category (91.4%). The results of the Chi-Square test obtained a p value = 0.007 (p